2011
DOI: 10.1109/tit.2011.2158874
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Networks Achieve Throughput Scaling of a Homogeneous Network

Abstract: We study two distinct, but overlapping, networks that operate at the same time, space, and frequency. The first network consists of n randomly distributed primary users, which form either an ad hoc network, or an infrastructuresupported ad hoc network with l additional base stations. The second network consists of m randomly distributed, ad hoc secondary users or cognitive users. The primary users have priority access to the spectrum and do not need to change their communication protocol in the presence of sec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(114 citation statements)
references
References 33 publications
1
109
0
4
Order By: Relevance
“…In [18], it is shown that under certain assumptions, which are valid in our proposed network model, both secondary and primary networks achieve the same throughput scaling as when the other network is absent. These assumptions include:…”
Section: B Scaling Lawsmentioning
confidence: 91%
“…In [18], it is shown that under certain assumptions, which are valid in our proposed network model, both secondary and primary networks achieve the same throughput scaling as when the other network is absent. These assumptions include:…”
Section: B Scaling Lawsmentioning
confidence: 91%
“…The capacity of general ad hoc networks has been extensively studied in literature [29,30]. The scaling laws of the throughput and/or delay of coexisting primary and secondary ad hoc networks under various protocol settings have been investigated in [29,[31][32][33]. These works consider fundamentally different problems than our study, which focuses on the achievable transmission capacity (link layer) of cognitive radio networks with cooperative relaying.…”
Section: Related Workmentioning
confidence: 99%
“…Since the capacity of the secondary user decreases with the increase of the power ratio, we can obtain the following maximum transmission capacity C * AF of the cooperative cognitive network by substituting γ l ps into Equation 32.…”
Section: Amplify-and-forwardmentioning
confidence: 99%
“…The capacity scaling law of CR networks has been analyzed in [4,5,6]. In [4], the authors also derive the capacity-delay tradeoff for a specific routing and scheduling algorithm which is shown to achieve the optimal one for homogeneous networks.…”
Section: B Related Workmentioning
confidence: 99%
“…We use the infinite connected component consisting of communication links 5 in G H (λ S , λ P T , t 0 ) during some primary slot t 0 to construct a path L C from µ to ν such that the multihop delay along this path is independent of the distance d(µ, ν) (see Fig. 4 …”
Section: Proof Of T21mentioning
confidence: 99%